2005
DOI: 10.1042/bj20051066
|View full text |Cite
|
Sign up to set email alerts
|

The intersubunit lock-and-key motif in human glutathione transferase A1-1: role of the key residues Met51 and Phe52 in function and dimer stability

Abstract: The dimeric structure of certain cytosolic GSTs (glutathione S-transferases) is stabilized by a hydrophobic lock-and-key motif at their subunit interface. In hGSTA1-1 (human class Alpha GST with two type-1 subunits), the key consists of two residues, Met51 and Phe52, that fit into a hydrophobic cavity (lock) in the adjacent subunit. SEC (size-exclusion chromatography)-HPLC, far-UV CD and tryptophan fluorescence of the M51A and M51A/F52S mutants indicated the non-disruptive nature of these mutations on the glob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 53 publications
1
12
0
Order By: Relevance
“…This value is very close to the predicted molecular weight of 171.2 KDa, which is the sum of 2 x 48.8 KDa (6xHis-FEZ1) and 2 x 36.8 KDa (GST-SCOCO). However, we must consider the dimerization of GST in this analysis [37-39]. To access exclusively the oligomeric state of the GST-SCOCO molecule when interacting with FEZ1 protein is not trivial because FEZ1 protein has many regions intrinsically disordered and most methods that allow us to estimate the molecular mass use globular proteins as standards.…”
Section: Resultsmentioning
confidence: 99%
“…This value is very close to the predicted molecular weight of 171.2 KDa, which is the sum of 2 x 48.8 KDa (6xHis-FEZ1) and 2 x 36.8 KDa (GST-SCOCO). However, we must consider the dimerization of GST in this analysis [37-39]. To access exclusively the oligomeric state of the GST-SCOCO molecule when interacting with FEZ1 protein is not trivial because FEZ1 protein has many regions intrinsically disordered and most methods that allow us to estimate the molecular mass use globular proteins as standards.…”
Section: Resultsmentioning
confidence: 99%
“…Hydrophobic interactions are known to be the most common motif for multimerisation of proteins. GST itself is known to stabilise its dimeric form through a hydrophobic lock-and-key motif [32]. Furthermore, several chaperones act as dimers, tetramers or oligomers, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…1D). The substitution of charged residues, such as Asp, Arg, and Glu into a protein dimer or oligomer interface has been shown to be a viable approach for preparing monomeric enzymes (25,(37)(38)(39).…”
Section: Resultsmentioning
confidence: 99%
“…A combination of evidence from size exclusion chromatography and multiangle static light scattering, a well known method for measurement of absolute molecular weight of macromolecules in solution (27,39), revealed that all three mutants were successfully destabilized to form monomers in solution (Figs. 2 and 3).…”
Section: Discussionmentioning
confidence: 99%